The initial statement is: QS = SU (1)
QR = TU (2)
We have to probe that: RS = ST
Take the expression (1): QS = SU
We multiply both sides by R (QS)R = (SU)R
But (QS)R = S(QR) Then: S(QR) = (SU)R (3)
From the expression (2): QR = TU. Then, substituting it in to expression (3):
S(TU) = (SU)R (4)
But S(TU) = (ST)U and (SU)R = (RS)U
Then, the expression (4) can be re-written as:
(ST)U = (RS)U
Eliminating U from both sides you have: (ST) = (RS) The proof is done.
I think 121
406 + 94 = 500 and 180 + 199 = 379.
Subtract that and 121 is what’s left.
"return on investment" is the best measure of the efficiency of an investment, but it should be noted that there are other indicators of how well an investment is doing.
Answer:
-2/3
Step-by-step explanation:
To find the slope we use the formula
m= ( y2-y1)/(x2-x1)
= ( 14-10)/(-18- -12)
= (14-10)/(-18+12)
= 4/-6
= -2/3